2022
DOI: 10.1039/d1tc06140b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochromic luminogens with hypsochromically shifted emission switching property: recent advances and perspectives

Abstract: Mechanofluorochromic (MFC) materials are a class of luminescent materials that have ability to show changes in their emission when subjected to various mechanical stimuli. A wide range of MFC materials...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 137 publications
(166 reference statements)
0
30
0
Order By: Relevance
“…This may be ascribed to the transformation of the packing arrangement and molecular configurations in the different states. 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be ascribed to the transformation of the packing arrangement and molecular configurations in the different states. 42…”
Section: Resultsmentioning
confidence: 99%
“…This may be ascribed to the transformation of the packing arrangement and molecular configurations in the different states. 42 Theoretical explorations were carried out in to verify the influence of the intramolecular charge transfer on the optical properties in this asymmetrical D-A system at the B3LYP/6-31g-(d) level. 43,44 As expected, the para substituted moieties on the terminal phenyl basically determined the distributions of their lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…45 Based on the different phenomena exhibited by the mechanochromic materials, mechanochromism can be classified into various groups, such as two-color and multicolor mechanochromism, 46 reversible and irreversible mechanochromism, 47 fluorescence–phosphorescence mechanochromism, 48 turn-on and turn-off type mechanochromism, 49 and bathochromically and hypsochromically shifted mechanochromism. 50…”
Section: Mechanochromismmentioning
confidence: 99%
“…8 Among the various MFC organic emitters, small molecules with defined molecular structures have been deeply explored compared to polymeric molecules, which exhibit limitations in terms of their synthetic difficulties, reproducibility, purity, and ill-defined molecular structure. 9,10 Although a few comparative studies of compounds displaying MFC behavior have been reported, 11–14 the MIEE features of carboxylic acid and ester molecules have hardly been investigated. 15,16 The molecular packing motif in the solid state is primarily directed by inter/intramolecular H-bonding interactions.…”
Section: Introductionmentioning
confidence: 99%